Structural tuning of organoruthenium compounds allows oxidative switch to control ER stress pathways and bypass multidrug resistance. Issue 7 (15th March 2016) - Chow, Mun Juinn; Licona, Cynthia; Pastorin, Giorgia; Mellitzer, Georg; Ang, Wee Han; Gaiddon, Christian
Abstract : Varying the arene ligand on organoruthenium compounds induced the differential activation of ER stress pathways, leading to non-apoptotic programmed cell death and bypassing drug resistance mechanisms. Abstract : Multidrug resistance (MDR) is a major impediment to the success of chemotherapy in many cancer types. One particular MDR mechanism is the inherent or acquired adaptation of the cellular survival pathways that render malignant cells resistant to apoptotic cell death. Since most drugs act through apoptosis, compounds capable of inducing alternative forms of programmed cell death (PCD) can potentially be harnessed to bypass MDR. We investigated two organoruthenium complexes, RAS-1H and RAS-1T, and demonstrated that although they both induced non-apoptotic PCD through ER stress pathways, their modes-of-action were drastically different despite modest structural variations. RAS-1T acted through ROS-mediated ER stress while RAS-1H was ROS-independent. We further showed that they were more efficacious against apoptosis-resistant cells compared to clinical drugs including oxaliplatin. This work provides the basis for underpinning ER stress modulation using metal complexes to bypass apoptosis resistance.